068 Immune checkpoint inhibitors: the neurologist's role. Issue 6 (27th May 2022) - Brown, Rachel; Spillane, Jennifer; Lunn, Michael; Zandi, Michael; Rees, Jeremy; Larkin, James; Turajlic, Samra; Carr, Aisling
Abstract : Over the last decade, immune checkpoint inhibitors (ICIs) have revolutionised treatment and outcomes for an increasing number of cancer types. By 'removing the breaks' they boost the anti-tumour immune response, but their effect is non-specific, and a number of systemic toxicities may arise. Neurological toxicity occurs in 1–14% patients depending upon the ICI regime used (Spain et al., 2016). We have developed a collaborative neurotoxicty service with the Royal Marsden Hospital, and demonstrate that early involve- ment of the neurologist is paramount to ensuring effective and efficient care in this patient group. To date, we have received 24 referrals regarding neurological symptoms in patients receiving ICIs. While half were due to ICI-related neurotoxicity, the remainder were caused by cancer progression (2), neurologi- cal side-effects of either other drugs (3) or systemic immune toxicities (2), or worsening/new 'conventional' neurological disorders (5). Therefore in addition to identifying and managing neurological toxicity, the role of the neurologist is to identify where neurological toxicity has not occurred, thus enabling the patient to be treated appropriately, while continuing with potentially life-saving immune therapy. With increasing use of these drugs, more robust understanding of risk, patterns and mechanisms of neurological injury must be established through collaborative, cross-disciplinary work to optimise outcomes in this patient group. rachel.brown@ucl.ac.uk